APPLICATION OF PHARMACEUTICAL KNOWLEDGE TO THE UNCONVENTIONAL USE OF A RARELY USED ANAESTHETIC AGENT. Issue 9 (17th August 2016) - Cole, Caroline
Abstract : Case summary: A 6 yr old 45 kg child with severe Cushinoid features was admitted to PICU with probable hypertensive encephalopathy. She presented with increasing headaches, vomiting and seizures becoming unresponsive with a GCS of 3. She was profoundly hypertensive and her cortisol levels were significantly elevated (>2000 nmol/L). Rapid reduction in cortisol levels was required to stabilise her condition prior to surgery. Etomidate is the only readily available intravenous preparation which reliably suppresses adrenocortical function. A continuous infusion was started at 2.5 mg/hr and escalated to 3.5 mg/hr to reduce cortisol levels to 200 nmol/L. Cortisol levels were monitored after 1, 2, 4, 8, 12 and 24 hr on starting and at regular intervals subsequently. Hydrocortisone 20 mg/m2/24 hr was introduced to balance the adrenal suppression and optimise cortisol levels to 200–800 nmol/L. Mineralocorticoid replacement with fludrocortisone became necessary, together with significant electrolyte replacement therapy. Surgery was delayed due to sepsis, and block and replace therapy was continued for a period of 3 weeks. During this time she experienced minimal sedative effects from the etomidate. Pharmacy contribution: Advice was given on the potential toxicity of pharmaceutical excipients. The aqueous formulation of etomidate contains propylene glycol and prolonged infusion can result in significant intake. Calculations revealed an intake of 350 mg/kg/day for this child with an infusion of 2.5 mg/hr etomidate. The WHO limit is 25 mg/kg/day when propylene glycol is used as a food additive.1 An acceptable limit for intravenous exposure has not been established. Children under 4 years have limited ability to metabolise propylene glycol and accumulation can occur. Potential toxicity includes hyperosmolality, metabolic acidosis, nephrotoxicity, arrhythmias and CNS toxicity. To obviate these risks, the alternative lipid formulation of etomidate was obtained. Blood samples were subsequently reported to be lipaemic and concerns were raised about the lipid load of this formulation. Calculations revealed that 0.3–0.5 g/kg/day lipid was being infused, which is significantly less than parenteral nutrition would provide. It is possible that blood samples were withdrawn from the line infusing etomidate resulting in lipaemia, but it is also likely that hypertriglyceridaemia was a result of her underlying condition. The pharmacist was involved in many other aspects of this child's care including advice on intravenous access, infusion preparation, drug compatibility and stability issues, electrolyte management and dosing of various drugs in obesity. Outcome: An ACTH secreting thymic tumour was resected. Hydrocortisone doses were adjusted perioperatively to cover the stress of surgery, and subsequently weaned post-operatively. Complete resection was not achieved and further block and replace therapy was used prior to bilateral adrenalectomy, followed by chemotherapy and radiotherapy. Lessons to be learnt: Pharmacists should evaluate the potential toxicity of excipients in medication, particularly when formulations are given by an unlicensed method of administration in children. Other parenteral products with a significant propylene glycol load include lorazepam, phenobarbital, phenytoin and co-trimoxazole.